The Factors of influencing consumer decision making in buying groceries between hypermarket and grocery shop in Batu Kawa - Bong, Kueh Yuan (Universiti Malaysia Sarawak (UNIMAS), 2015)
Retail industry is expected growth faster rate especially in Batu Kawa, Kuching due to numerous latest developments in tenn of shop-lot, housing and others. This definitely will bring significant contribution towards economic growth and financial prospects. The retail industries such as hypennarket, supennarket, and grocery shop is able bring convenience in tenn of supply various goods to our daily life. This study was designed to identify the factors influencing consumer decision making in buying groceries between hypennarket and grocery shop in Batu Kawa. The factors were tested in this study included product's price, product's quality, brand image, availability of product, and convenience of stores. Furthennore, the data collection method in this study was using quantitative research which is distribution of question by convenience sampling method. 384 respondents from Batu Kawa which is targeted the consumer that has consists purchasing power in their daily life. Apart from that, the hypothesis in this study was tested by using the Standard Multiple Regression and Pearson's Correlation Coefficient.